The Effect of Addition of Sugarcane Ash Waste and Low Density Polyethylene Plastic on the Characteristics of Laston AC-WC Mixture - Heru Prasetyo Nugroho; Heri Sujatmiko; Hari Pranoto (Universitas Islam Raden Rahmat, Malang, 2025)
Bagasse ash has pozzolanic properties which contain chemical compounds in the form of Silica (SiO2) and act as fillers and Low-Density Polyethylene (LDPE) plastic has the same plastomer properties as asphalt thermoplastic properties. Both of these wastes can be used as substitute materials for the Laston AC-WC mixture. This exploration aims to determine the effect of adding sugarcane bagasse ash and LDPE plastic on the characteristics of the Laston AC-WC mixture. The variations in the levels of bagasse ash added were 25%, 50%, 75%, and 100% of the filler weight and LDPE 5%, 5.55%, and 6% of the total asphalt weight. After the Marshall test was carried out, the Laston AC-WC mixture with the addition of bagasse ash and LDPE could increase the stability value compared to the asphalt mixture without the addition of waste. The optimum asphalt content value is found in a mixture of 75% bagasse ash and 6% LDPE content because it has the highest stability value and other Marshall test values ​​are in accordance with the 2019 Hot Asphalt Mix Design and Implementation Guidelines for Utilizing Plastic Waste.